The Linguistic Analysis of Deduction in The Holy Qur'an: Surat Ghafir as a Model - هاجر احمد رشيد (College of Education for Women, 2019)
This paper aims at discovering the real implication of deduction in the Arabic culture with concentration on its applications in Arabic grammar, logic, and fundamentals of Islamic legislations. Some light has been shed on deduction in the Arabic culture but most of recent works did not analyze deduction according to the pragmatic analysis. This paper will answer the following questions:  to what extent deduction in Arabic grammar could comprehend with deduction l logic and fundamentals of thinking in Islamic thought?  how can we find the deduction thinking in the Qur'anic surah if Ghafir?  Can we find parts of deduction in the surah? The methodology in this paper is descriptive analytical. This methodology has been chosen according to the pragmatic thinking which concentrates on description and analysis simultaneously. The following results have been ended up with:  A comprehensive thinking collection between grammar, fundamental research, and logic in the applications of the Arabic culture.  This collection seems to be clear in their understanding in the Qur'anic text including the referred to surah.  The following part of deduction is clearly understood from the surah of Ghafir: the gradual, backward, complex, and pronominal deductions.